2006
DOI: 10.5194/bg-3-135-2006
|View full text |Cite
|
Sign up to set email alerts
|

Sources of nitrous oxide emitted from European forest soils

Abstract: Abstract. Forest ecosystems may provide strong sources of nitrous oxide (N 2 O), which is important for atmospheric chemical and radiative properties. Nonetheless, our understanding of controls on forest N 2 O emissions is insufficient to narrow current flux estimates, which still are associated with great uncertainties. In this study, we have investigated the quantitative and qualitative relationships between N-cycling and N 2 O production in European forests in order to evaluate the importance of nitrificati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 33 publications
5
75
1
Order By: Relevance
“…It appeared that nitrification contributed very little to N 2 O production within the observed WFPS range. This was in contrast to several other studies (Bateman and Baggs 2005;Mathieu et al 2006;Zhang et al 2011a;Khalil et al 2004;Ambus et al 2006;Mørkved et al 2006;Russow et al 1994;Wolf and Brumme 2002;Wolf and Russow 2000;Eickenscheidt et al 2011) who found that significant contributions of nitrification to N 2 O production occurred at intermediate WFPS ranges whereas denitrification generally occurred at high soil moisture content. Comparing soil types in the above cited studies, it appears that also soil pH could be an important factor for N 2 O source partitioning, as it interacts with the soil moisture relationship; in neutral to alkaline soils the contribution of nitrification to N 2 O emission seems to be high and less sensitive to WFPS than the contribution of denitrification (Khalil et al 2004;Mathieu et al 2006;Bateman and Baggs 2005).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It appeared that nitrification contributed very little to N 2 O production within the observed WFPS range. This was in contrast to several other studies (Bateman and Baggs 2005;Mathieu et al 2006;Zhang et al 2011a;Khalil et al 2004;Ambus et al 2006;Mørkved et al 2006;Russow et al 1994;Wolf and Brumme 2002;Wolf and Russow 2000;Eickenscheidt et al 2011) who found that significant contributions of nitrification to N 2 O production occurred at intermediate WFPS ranges whereas denitrification generally occurred at high soil moisture content. Comparing soil types in the above cited studies, it appears that also soil pH could be an important factor for N 2 O source partitioning, as it interacts with the soil moisture relationship; in neutral to alkaline soils the contribution of nitrification to N 2 O emission seems to be high and less sensitive to WFPS than the contribution of denitrification (Khalil et al 2004;Mathieu et al 2006;Bateman and Baggs 2005).…”
Section: Discussioncontrasting
confidence: 54%
“…However, the contribution of nitrification was not addressed in this study. In a laboratory incubation experiment with acidic soils from 11 different forest sites across Europe, Ambus et al (2006) found that NO 3 -contributed on average 62 % to N 2 O production while NH 4…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, different approaches and techniques, including inhibition of low concentration of acetylene on nitrification, 15 N trace methods, natural abundance of 15 N in N 2 O, and 15 N tracing model, are applied to identify the pathways and rates of soil N 2 O production, which have been well summarized by Müller et al (2014) and Kulkarni et al(2014). For example, Ambus et al (2006) found the main source of N 2 O emitted from temperate European forests characterized by various climatic regimes and forest types (seven coniferous sites and four deciduous sites) is nitrification following the application of laboratory 15 N labeling of intact soil cores and linear mixing model. Furthermore, a low-concentration 15 N-labeled ammonium-nitrate solution was applied to a temperate beech and spruce forest to simulate N deposition and thus to assess the direct contribution of N deposition to N 2 O emissions in temperate forests, with the results showing that stimulated N loss as N 2 O was mainly driven by denitrification (Eickenscheidt et al 2011).…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 99%
“…Nitrous oxide (N 2 O) is among the most important greenhouse gases, contributing by 6% to global warming (Loubet et al 2011;Ranucci et al 2011), and directly affects the stratospheric ozone layer (Willianms et al 1992;Ravishankara et al 2009). Nitrous oxide emitted from soils leads to N loss from the ecosystem and is produced by nitrification and denitrification microbiological activities (Skiba et al 1993;Ambus et al 2006;Jiang-Gang et al 2007;Senbayram et al 2012) and chemodenitrification at low pH (< 5.5) (Van Cleemput, Samater 1996). The major N 2 O source is denitrification (Skiba et al 1997;Skiba, Smith 2000;Ruser et al 2001).…”
mentioning
confidence: 99%